Openness to experience as mediator of the relationship between product creativity and purchase intention - Tan, Chee-Seng (Penerbit Universiti Kebangsaan Malaysia, 2016)
Although past studies have found a positive relationship between product creativity and purchase in-tention, little is known about the underlying process behind this relationship. The present study ad-dressed this gap by examining the role of openness to experience in the relationship between product creativity and purchase intention. Participants (88 undergraduate students) evaluated creativity of a self-nominated product and reported the extent to which they are willing to buy the product, as well as their openness to experience. Analysis showed that there was a positive relationship between product creativity and openness to experience and these two variables were significantly correlated with pur-chase intention. Furthermore, mediation analysis supported that product creativity increases purchase intension indirectly through openness to experience. The findings shed light on the mechanism of how product creativity increases purchase intention and serve as an evidence for future studies to investigate how and what aspects of product creativity that enhance individual’s sense of openness and purchase intention.